2023
DOI: 10.1038/s41598-023-38454-6
|View full text |Cite
|
Sign up to set email alerts
|

A punctuated equilibrium analysis of the climate evolution of cenozoic exhibits a hierarchy of abrupt transitions

Abstract: The Earth’s climate has experienced numerous critical transitions during its history, which have often been accompanied by massive and rapid changes in the biosphere. Such transitions are evidenced in various proxy records covering different timescales. The goal is then to identify, date, characterize, and rank past critical transitions in terms of importance, thus possibly yielding a more thorough perspective on climatic history. To illustrate such an approach, which is inspired by the punctuated equilibrium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Thus, a better understanding of these tipping mechanisms becomes essential through, for example, the study of the evolution of the Earth climate in the past (Wunderling et al, 2023). Signatures of global climatic transitions are indeed found in paleoclimate proxy records for several periods of Earth's history (Messori and Faranda, 2021;Boers et al, 2022), as during the Snowball Earth episodes in the Neoproterozoic era (Hoffman et al, 1998;Pierrehumbert, 2005;Hoffman et al, 2017;Eberhard et al, 2023), the Eocene-Oligocene transition (Hutchinson et al, 2021), the glacial-interglacial cycles (Ferreira et al, 2018;Riechers et al, 2022), the whole Cenozoic, from 66 Ma to present (Westerhold et al, 2020;Rousseau et al, 2023), or the climatic oscillations observed at the Smithian-Spathian boundary in the Early Triassic (Widmann et al, 2020), just after the Permian-Triassic mass extinction (∼ 252 Ma), the most severe of the Phanerozoic (Raup, 1979;MacLeod, 2014;Stanley, 2016). However, our knowledge of deep-time climates is subject to large uncertainties and their numerical modelling needs to consider, in general, a wide range of initial and boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of these tipping mechanisms becomes essential through, for example, the study of the evolution of the Earth climate in the past (Wunderling et al, 2023). Signatures of global climatic transitions are indeed found in paleoclimate proxy records for several periods of Earth's history (Messori and Faranda, 2021;Boers et al, 2022), as during the Snowball Earth episodes in the Neoproterozoic era (Hoffman et al, 1998;Pierrehumbert, 2005;Hoffman et al, 2017;Eberhard et al, 2023), the Eocene-Oligocene transition (Hutchinson et al, 2021), the glacial-interglacial cycles (Ferreira et al, 2018;Riechers et al, 2022), the whole Cenozoic, from 66 Ma to present (Westerhold et al, 2020;Rousseau et al, 2023), or the climatic oscillations observed at the Smithian-Spathian boundary in the Early Triassic (Widmann et al, 2020), just after the Permian-Triassic mass extinction (∼ 252 Ma), the most severe of the Phanerozoic (Raup, 1979;MacLeod, 2014;Stanley, 2016). However, our knowledge of deep-time climates is subject to large uncertainties and their numerical modelling needs to consider, in general, a wide range of initial and boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of these tipping mechanisms becomes essential through, for example, the study of the evolution of Earth's climate in the past (Wunderling et al 2023). Signatures of global climatic transitions are indeed found in paleoclimate proxy records for several periods of Earth's history (Messori and Faranda 2021;Boers et al 2022), such as during the Snowball Earth episodes in the Neoproterozoic era (Hoffman et al 1998;Pierrehumbert 2005;Hoffman et al 2017;Eberhard et al 2023), the Eocene-Oligocene transition (Hutchinson et al 2021), the glacialinterglacial cycles (Ferreira et al 2018;Riechers et al 2022), and the whole Cenozoic, from 66 Ma to present (Westerhold et al 2020;Rousseau et al 2023).…”
Section: Introductionmentioning
confidence: 99%